Analysis and research on experimental model of exercise-induced fatigue - Zhong, H.; Wang, C.; Wan, Z.; Lei, J. (Frontiers in Educational Research, 2019)
Exercise-induced fatigue is a common physiological phenomenon for all of the athletes, and it is a research hotspot in the field of sports and sports medicine. How to cause exercise-induced fatigue is a very important step for this kind of research. This article analyses and researches the experimental models of exercise-induced fatigue used by researchers in the previous studies. There are two kinds of experimental model of exercise-induced fatigue, which include animal models and human models. Then, each model has many different examples.